Old Testament commentary survey - Longman, Tremper 1952- (Grand Rapids, MI Baker Academic, 2003)
Includes index.
Keywords: Bible. O.T. -- commentaries -- bibiography; Bible. O.T. -- commentaries -- history and criticism